Are feral goats intermediate hosts for Linguatula (Pentastomida) in Australia?. (August 2022) - Barton, Diane P.; Shackelford, Bridgette; Shamsi, Shokoofeh; Jenkins, David
Abstract: Feral goats, Capra hircus (Bovidae), currently occur across 28% of Australia, and are found in all states and territories as well as some offshore islands. Feral goats are harvested for live export or processed as game meat, with feral goats making up approximately 90% of goats sent to slaughter in Australia. Nymphs of the pentastomid parasite, Linguatula serrata, are common parasites of goats elsewhere in the world, where they cause Halzoun or Marrara disease in humans through the consumption of nymphs in raw or semi-cooked edible offal. Despite being commonly encountered in cattle at slaughter in Australia, L. serrata nymphs have never been reported from feral goats in Australia. Goats at slaughter, however, commonly show infections of lymph nodes, the majority of which are diagnosed as caseous lymphadenitis caused by bacteria, although a small number have no known aetiology. Examination of 33 feral goats from locations in New South Wales and South Australia found a Linguatula sp. nymph encased in the mesenteric lymph node of one goat from the Cooma region of New South Wales. The potential risk of transmission of Linguatula sp. to humans and other domestic animals is discussed. This study has highlighted the importance of continued surveys of feral animals for infection with parasites, especially as their distribution changes. Graphical abstract: Image 1 Highlights: An infective nymphal Linguatula sp. was collected from the lymph nodes of a feral goat in Australia. This is the first report of the feral goat as an intermediate host for Linguatula in Australia. Linguatula poses a zoonotic risk. The importance of continued surveys of parasites of feral animals is highlighted.